Graphic representation of statistics, what fun? And what is this for? - MAHAMMED, Yahia LAMARA (Social Empowerment Journal, 2024)
Statistics plays an essential role in the realization of many scientific researches and university theses given the rapid development of information technologies, computing and statistical methods, such as Excel tables and the statistical program SPSS, which made it easier to process data that was previously difficult to process. And because of the apparent lack of use of graphs and tables of all kinds, and of the errors made in the field studies which are carried out as part of the end of studies, and with the aim of dispelling fear or mental heaviness in those who avoid statistics and these representations in particular, despite its graphic importance, its explanatory effectiveness, and the pleasure and suspense it gives to figures, percentages and averages, in this work, using the descriptive approach, we decided to highlight the most important problems related to the representation of data on social phenomena previously organized in frequency tables and statistics, and from there, to transfer the modern statistical flavor to students and researchers in general by presenting the concept and characteristics of graphical representation and its most important formal components, while examining its types and various common usage errors.